THE INFLUENCE OF SOCIAL SUPPORT AND NON-PHYSICAL WORK ENVIRONMENT ON NURSE ANXIETY DURING THE COVID-19 PANDEMIC IN TABANAN HOSPITAL - I Nengah Wira Wijaya; Cokorda Bagus Jaya Lesmana (Jurnal Delima Harapan, 2023)
Anxiety in health care workers can be detrimental to health care. Support from family, loved ones, workplaces and the environment is important for nurses because people under stress need advice, solutions and care to ease their worries about the COVID-19 situation. This study aims to determine the effects of social support and non-physical work environment on the anxiety of nurses during the COVID-19 pandemic at Tabanan Hospital. This study used a cross-sectional method of observational study design. This study will be conducted at Tabanan hospital from May to June 2022 with 82 nurses selected from the entire sample. Different topics include social support and non-physical work and anxiety for nurses during the COVID-19 pandemic. Data were collected from questionnaires and analyzed using logistic regression analysis with 95% confidence intervals. RESULTS: In this study, nurses in physical workplaces were found to experience stress 21 times (OR=21.482, p-value=<0.001) compared to nurses in physical workplaces. Nurses with positive social support experienced 7 times less anxiety than nurses with positive social support (OR=6.823, p value=<0.010).The prevalence of nursing anxiety during the COVID-19 outbreak at Tabanan Hospital is 64.6%. Social support and work environment were not physical variables related to anxiety (p<0.05). The prevalence of anxiety among nurses during the COVID-19 pandemic in Tabanan Hospital is 64.6%, which is 58.5% mild anxiety, 6.1% moderate anxiety. Social support variables and non-physical work environment variables influence anxiety (p < 0.05). no less than 92.9% of nurses with good social support had no fear. no less than 89.3% of nurses with a good non-physical work environment had no fear. Nurses with a sufficiently demanding physical work environment experienced anxiety 21 times (OR = 21.482, p value = <0.001) compared to nurses with a good physical work environment. Nurses with adequate social support were less depressed and experienced anxiety 7 times (OR = 6.823, p value = <0.010) compared to nurses with good social support